2021
DOI: 10.1001/jamanetworkopen.2021.29906
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sleep and Attention Metrics Among Nurses Working Shifts on a Forward- vs Backward-Rotating Schedule

Abstract: IMPORTANCEThe association of fast backward-rotating shift work (ie, anticlockwise sequence of afternoon, morning, and night shifts) with subjective and objective measures of sleep-wake quality, daytime attention, and tiredness of health care workers has not yet been established. OBJECTIVE To investigate the association of shift rotation direction with tiredness, sleepiness, and sustained attention among nurses working forward-and backward-rotating shifts. DESIGN, SETTING, AND PARTICIPANTS Data of this cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…This may have affected the results for those going from intervention to control. Fifth, as mentioned above, a backward rotation is not an appropriate shift system in terms of the circadian rhythm [ 25 , 26 ]. The shift schedule intervention basically remained as a backward rotation while this intervention study extended restart breaks after consecutive night shifts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have affected the results for those going from intervention to control. Fifth, as mentioned above, a backward rotation is not an appropriate shift system in terms of the circadian rhythm [ 25 , 26 ]. The shift schedule intervention basically remained as a backward rotation while this intervention study extended restart breaks after consecutive night shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Two three-shift schedules rotate in a forward direction (day shift to evening shift to night shift) and a backward direction (night shift to evening shift to day shift). Earlier studies have suggested that a backward rotation could be more difficult to adapt to than a forward rotation because the circadian rhythm tends to move forward [ 25 , 26 ]. For example, compared with forward-rotating schedules, backward-rotating shift systems showed a relative risk of 2.9 due to an increased need for recovery and a risk of 3.2 due to poor general health [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Zare et al, 2017); establishing reasonable and flexible shift scheduling by considering the characteristics of the shift system, such as the length of shifts, the direction and speed of shift rotation, and the length of the recovery period in between two consecutive shifts, etc. (Alfonsi et al, 2021;Di Muzio et al, 2021;Sun et al, 2019)).…”
Section: Correlations Between Work Stress Circadian Rhythm and Sleep ...mentioning
confidence: 99%
“…Night-shift work was developed in hospitals to ensure high-quality care; however, it leads to circadian misalignment and poor sleep quality among nurses ( Di Muzio et al, 2021 ). The internship period is the duration for interns to acclimate to night-shift work.…”
Section: Introductionmentioning
confidence: 99%